2023
DOI: 10.3389/fnins.2023.1231273
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional connectivity patterns associated with symptoms of vestibular migraine

Xia Zhe,
Hailian Zhang,
Min Tang
et al.

Abstract: BackgroundSeveral functional magnetic resonance imaging (fMRI) investigations of patients with vestibular migraine (VM) have revealed abnormal functionality in different networks, indicating that VM is related to alterations in brain function. We sought to investigate the resting-state functional connectivity (FC) patterns during the interictal period in VM by combining data-driven voxel-wise degree centrality (DC) calculations and seed-based FC analyses, and thereby determine the associations between cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Thus, the increased FC between right PreCG and regions of left cuneus and LG suggested enhanced functional connections between motor and visual networks. Similar to our study, previous MRI studies on VM have reported the functional changes in the cuneus and LG [ 17 , 24 , 61 ]. Additionally, we found that the FC between right PreCG and right LG was positively correlated with the frequency of vestibular symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the increased FC between right PreCG and regions of left cuneus and LG suggested enhanced functional connections between motor and visual networks. Similar to our study, previous MRI studies on VM have reported the functional changes in the cuneus and LG [ 17 , 24 , 61 ]. Additionally, we found that the FC between right PreCG and right LG was positively correlated with the frequency of vestibular symptoms.…”
Section: Discussionsupporting
confidence: 92%